2007
DOI: 10.1359/jbmr.070103
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Blinded Analysis of RT-PCR Detection Methods for Paramyxoviruses in Relation to Paget's Disease of Bone

Abstract: Conflicting results have been reported on the detection of paramyxovirus transcripts in Paget's disease, and a possible explanation is differences in the sensitivity of RT-PCR methods for detecting virus. In a blinded study, we found no evidence to suggest that laboratories that failed to detect viral transcripts had less sensitive RT-PCR assays, and we did not detect measles or distemper transcripts in Paget's samples using the most sensitive assays evaluated.Introduction: There is conflicting evidence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 46 publications
1
36
0
1
Order By: Relevance
“…As paramyxoviruses interfere with both IFN production and signalling, there is potentially a mechanistic link between these observations. Others have disputed this link (Nuovo et al, 1992;Ooi et al, 2000;Rima et al, 2002;Ralston et al, 2007), but the picture is complicated by the fact that most paramyxoviruses, and many other viruses, block the IFNsignalling pathways, raising the possibility that persistent infections by different viruses may cause the same manifestations of a chronic disease. Indeed, a number of different paramyxoviruses, including MeV, canine distemper virus (CDV), RSV, PIV3 and PIV5, have been reported to infect osteoclasts persistently (Mills et al, 1984;Basle et al, 1985Basle et al, , 1986Basle et al, , 1987Gordon et al, 1991;Mee et al, 1998;Reddy et al, 1999;Friedrichs et al, 2002;Hoyland et al, 2003).…”
Section: Consequences For the Virus And Hostmentioning
confidence: 99%
“…As paramyxoviruses interfere with both IFN production and signalling, there is potentially a mechanistic link between these observations. Others have disputed this link (Nuovo et al, 1992;Ooi et al, 2000;Rima et al, 2002;Ralston et al, 2007), but the picture is complicated by the fact that most paramyxoviruses, and many other viruses, block the IFNsignalling pathways, raising the possibility that persistent infections by different viruses may cause the same manifestations of a chronic disease. Indeed, a number of different paramyxoviruses, including MeV, canine distemper virus (CDV), RSV, PIV3 and PIV5, have been reported to infect osteoclasts persistently (Mills et al, 1984;Basle et al, 1985Basle et al, , 1986Basle et al, , 1987Gordon et al, 1991;Mee et al, 1998;Reddy et al, 1999;Friedrichs et al, 2002;Hoyland et al, 2003).…”
Section: Consequences For the Virus And Hostmentioning
confidence: 99%
“…Further, CDV N gene was identified by in situ hybridisation and RT-PCR from bone cells of dogs diagnosed with metaphyseal osteopathy , a canine bone disease of uncertain etiology but with some similar histological features of PDB . However, antagonistic results not in support of this theory were observed by PCR (RALSTON et al, 1991), while a comparative blinded study has suggested that cross-contamination due to the excessive usage of various diagnostic techniques, within the same laboratory, to evaluate the participation of CDV in PDB could have been responsible for the results described by MEE and collaborators (RALSTON et al, 2007).…”
Section: Public Health Concernsmentioning
confidence: 99%
“…The most widely studied environmental exposure is paramyxoviral infection, although evidence in favor of a viral etiology for PDB remains controversial [30][31][32]. The introduction of immunization programs for measles and distemper in the 1960s has been suggested as a possible reason for the reduction in incidence of PDB, but it has recently been highlighted that this occurred too recently to account for a reduction in prevalence and severity of PDB patients born in the 1930s and 1940s, assuming that a slow viral infection picked up in childhood was indeed the cause of the disease [13,14].…”
mentioning
confidence: 99%